Is There Synchronicity in Nitrogen Input and Output Fluxes at the Noland Divide Watershed, a Small N-Saturated Forested Catchment in the Great Smoky Mountains National Park? - H. Van Miegroet; I.F. Creed; N.S. Nicholas; D.G. Tarboton; K.L. Webster; J. Shubzda; B. Robinson; J. Smoot; D. W. Johnson; S. E. Lindberg; G. Lovett; S. Nodvin; et al. (The Scientific World Journal)
High-elevation red spruce [Picea rubens Sarg.]-Fraser fir [Abies fraseri (Pursh.) Poir] forests in the Southern Appalachians currently receive large nitrogen (N) inputs via atmospheric deposition (30 kg N ha1 year1) but have limited N retention capacity due to a combination of stand age, heavy fir mortality caused by exotic insect infestations, and numerous gaps caused by windfalls and ice storms. This study examined the magnitude and timing of the N fluxes into, through, and out of a small, first-order catchment in the Great Smoky Mountains National Park. It also examined the role of climatic conditions in causing interannual variations in the N output signal. About half of the atmospheric N input was exported annually in the streamwater, primarily as nitrate (NO3-N). While most incoming ammonium (NH4-N) was retained in the canopy and the forest floor, the NO3-N fluxes were very dynamic in space as well as in time. There was a clear decoupling between NO3-N input and output fluxes. Atmospheric N input was greatest in the growing season while largest NO3-N losses typically occurred in the dormant season. Also, as water passed through the various catchment compartments, the NO3-N flux declined below the canopy, increased in the upper soil due to internal N mineralization and nitrification, and declined again deeper in the mineral soil due to plant uptake and microbial processing. Temperature control on N production and hydrologic control on NO3-N leaching during the growing season likely caused the observed inter-annual variation in fall peak NO3-N concentrations and N discharge rates in the stream.